The effects of ciprofloxacin on early life stages of common carp (Cyprinus carpio). (14th April 2016) - Zivna, Dana; Plhalova, Lucie; Chromcova, Lucie; Blahova, Jana; Prokes, Miroslav; Skoric, Misa; Marsalek, Petr; Praskova, Eva; Stepanova, Stanislava; Svobodova, Zdenka
Abstract: The authors performed a toxicity test with ciprofloxacin in fertilized eggs of common carp according to guideline 210 of the Organisation for Economic Co‐operation and Development. The tested concentrations were 1 μg L −1, 100 μg L −1, 500 μg L −1, 1000 μg L −1, and 3000 μg L −1 . Accelerated hatching was found in all groups exposed to ciprofloxacin, but significant growth reduction was found only in the group exposed to the highest concentration (3000 μg L −1 ). Increased numbers of macroscopic morphological anomalies were observed on day 6 of the test (after hatching). The highest numbers of macroscopic morphological anomalies were observed in the groups of free embryos and larvae exposed to ciprofloxacin concentrations of 100 μg L −1, 500 μg L −1, 1000 μg L −1, and 3000 μg L −1 (20−23% of tested samples). A gradual decrease in glutathione S‐transferase activity was detected in all experimental groups exposed to ciprofloxacin, but significant differences ( p < 0.01) were found only in groups treated with 500 μg L −1 and 3000 μg L −1 . Glutathione peroxidase and catalase exhibited increased activity in most of the tested concentrations ( p < 0.01 and <0.05, respectively), whereas decreased glutathione reductase activity was found in the groups exposed to ciprofloxacin concentrations of 500 μg L −1 and 3000 μg L −1 ( p < 0.05). The concentration of thiobarbituric acid–reactive substances was significantly lower ( p < 0.01) in all experimental groups exposed to ciprofloxacin. The lowest‐observed‐effect concentration of ciprofloxacin was 1 μg L −1 . These results suggest that hatching, early ontogeny, occurrence of morphological anomalies, antioxidant and biotransformation enzyme activity, and lipid peroxidation in fish can be affected by ciprofloxacin. Environ Toxicol Chem 2016;35:1733–1740. © 2015 SETAC